2022
DOI: 10.3390/curroncol29020097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prognostic Risk Factors and Establishment of Prognostic Scoring System for Secondary Adult Hemophagocytic Syndrome

Abstract: Introduction: The objective of this paper is to identify the prognostic risk factors of secondary adult hemophagocytic syndrome (HLH) in hospitalized patients and establish a simple and convenient prognostic scoring system. Method:We reviewed 162 adult patients secondary with HLH treated in Zhejiang Cancer Hospital and the First Affiliated Hospital of Medical College of Zhejiang University from January 2014 to December 2018 were enrolled to form the test group; from January 2019 to February 2021, 162 adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Although ferritin is a non-specific test for HLH diagnosis in Systemic Inflammatory Response Syndrome [37] and hematologic malignancy [38], test results can guide a physician to proceed with more investigations to complete the HLH-2004 criteria and HScore and avoid a delayed diagnosis. Hypoalbuminemia (<2 g/dL), high LDH level (>1,000 U/L), and prolonged PTT (>36 s) were not found to be correlated with poor outcomes in our study [20,34,39,40]. However, a platelet count <20 × 10 9 /L was associated with poor survival in the univariate analysis [20].…”
Section: Discussioncontrasting
confidence: 59%
“…Although ferritin is a non-specific test for HLH diagnosis in Systemic Inflammatory Response Syndrome [37] and hematologic malignancy [38], test results can guide a physician to proceed with more investigations to complete the HLH-2004 criteria and HScore and avoid a delayed diagnosis. Hypoalbuminemia (<2 g/dL), high LDH level (>1,000 U/L), and prolonged PTT (>36 s) were not found to be correlated with poor outcomes in our study [20,34,39,40]. However, a platelet count <20 × 10 9 /L was associated with poor survival in the univariate analysis [20].…”
Section: Discussioncontrasting
confidence: 59%
“…Otrock et al [10] found that only malignancy was an independent risk factor for a poor prognosis. Some singlecenter studies from China discovered other parameters that impacted prognosis in adult HLH including IL-10 ≥129 pg/mL, male, IL-6 ≥18.59 pg/mL, APTT >36 s, LDH >1,000 U/L, and CRP >100 mg/L [11,14,23]. A multicenter study suggested that gender, platelet count, albumin, ALT, and treatment regimens were independent prognostic factors for HLH in adults [24].…”
Section: Discussionmentioning
confidence: 99%
“…Upon TSM diagnosis, antibiotics were promptly adjusted to Amb. Furthermore, if a male patient presents with an activated partial thromboplastin time greater than 36 s, LDH greater than 1000 U/L, and CRP greater than 100 mg/L, this combination is consistently associated with a poor prognosis for HLH [24] . Our patient has been undergoing follow-up at the outpatient department for infectious diseases for three years post-discharge, and currently, their condition remains effectively controlled without any signs of recurrence.…”
Section: Discussionmentioning
confidence: 99%